Infection of domestic pigs with a genotype II potent strain of ASFV causes cytokine storm and lymphocyte mass reduction - Zuo, Xuezhi; Peng, Guorui; Zhao, Junjie; Zhao, Qizu; Zhu, Yuanyuan; Xu, Yuan; Xu, Lu; Li, Fangtao; Xia, Yingju; Liu, Yebing; Wang, Cheng; Wang, Zhen; et al. (Frontiers in Immunology, 2024)
The whole-genome sequence of an African swine fever virus (ASFV) strain (HuB/HH/2019) isolated from Hubei, China, was highly similar to that of the Georgia 2007/1 strain ASFV. After infection with strong strains, domestic pigs show typical symptoms of infection, including fever, depression, reddening of the skin, hemorrhagic swelling of various tissues, and dysfunction. The earliest detoxification occurred in pharyngeal swabs at 4 days post-infection. The viral load in the blood was extremely high, and ASFV was detected in multiple tissues, with the highest viral loads in the spleen and lungs. An imbalance between pro-and anti-inflammatory factors in the serum leads to an excessive inflammatory response in the body. Immune factor expression is suppressed without effectively eliciting an immune defense. Antibodies against p30 were not detected in acutely dead domestic pigs. Sequencing of the peripheral blood mononuclear cell transcriptome revealed elevated transcription of genes associated with immunity, defense, and stress. The massive reduction in lymphocyte counts in the blood collapses the body's immune system. An excessive inflammatory response with a massive reduction in the lymphocyte count may be an important cause of mortality in domestic pigs. These two reasons have inspired researchers to reduce excessive inflammatory responses and stimulate effective immune responses for future vaccine development.